(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
This study was conducted to find out how effective the strategies adopted by supervisors in managing work related stress in the Nigerian petroleum industry are. The study was grounded on the Person–Environment fit theory, with a multiple case study design as the choice design. The population for the study was supervisors in petroleum companies in the Nigeria Niger Delta region who have successfully applied strategies to reduce workrelated stress. Purposive sampling technique was adopted to sample six supervisors from three companies to participate in the study. The instrument for data collection was a structured interview guide and company document analysis. Results from the study showed that supervisor–worker relationship, creating a culture of co-worker support and mentoring of workers on stress management were part of the effective strategies does not require any significant financial implications from the company. Other effective strategies identified in the study that require some significant financial implications on the part of the company include workers training to enhance competency for assigned roles, hiring of additional workers to enable effective time-off schedule and shift rotation, investments in occupational health programs, payment for offsite recreational or social events, and workers compensation to ensure worker–pay match. The study concluded that appropriate utilization of these strategies may reduce the adverse effects of work related stress on worker’s health and improve profitability of the petroleum industry